PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DI DESA PINAMORONGAN KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - KUMAJAS, NOVLIN SANTIKA RUTH; TAMPI, GUSTAAF; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine the performance of the Village Consultative Body in PinamoronganVillage, Tarerean District, South Minahasa Regency. This study used qualitative research methods. Based onthe problems encountered, in carrying out its duties and responsibilities, the Village Consultative Body inPinamorongan Village has not been optimal in carrying out supervision of village administration inPinamorongan village. And based on the results of the research, the members of the Village Consultative Bodyin Pinamorongan Village still lack self-awareness of their duties and responsibilities and there are also somemembers who are inactive and lack a positive response from the village community.Keywords: Implementation , Village Consultative Body, Village Government